Abdominal tuberculosis: a study of 50 cases - Darbari, Ashutosh; Jauhari, Abhinav; Darbari, Geetika; Shrivastava, Vartika; Shrivastava, Ambuj (International Journal of Research in Medical Sciences, 2017)
Background: The main type of tuberculosis of interest to any hospital- based surgeon is intestinal, the clinical presentation of which varies from one of an acute abdomen to one of a protracted cause of ill health and morbidity with a notorious reputation for poor response to therapy, both conservative as well as surgical. Low socio- economic status and malnutrition in our country are very important causes of the high prevalence of pulmonary tuberculosis, and with superadded problems of overcrowding and poor access to good sanitation and neglect for medical attention, extra pulmonary forms of tuberculosis also form a sizeable proportion of the case load of tuberculosis. The major source of infection is the open untreated case of pulmonary tuberculosis. Methods: Presented here is a brief account of hospital- based study of the presentation of 50 cases of abdominal tuberculosis and its management in both the acute as well as chronic setting, carried out at the B. Y. L. Nair Municipal Hospital Mumbai. Results: In our study 40% patients presented with signs of intestinal obstruction, 6% with perforative peritonitis, 34% with diffuse or well defined lump and 54% with ascites. All these patients underwent biochemical, radiological and endoscopic investigations.All the cases in this study were put on antitubercular four drug regime. Isoniazid (5mg / kg), Rifampicin (5-10mg/kg), Ethambutol (15mg/kg) and Pyrazinamide (20-25mg/kg) for two months followed by Isoniazid and Rifampicin for seven months. None of the patients developed drug toxicity during treatment. In our study out of 50 patients, 24 patients were treated conservatively. These includes 12 with tuberculous peritonitis (2 of the 12 had associated paraortic lymphadenopathy), 6 with subacute intestinal obstruction, 4 with RIF lump and 2 with colonic pathology) were treated conservatively. 26 patients underwent surgical treatment. Out of these 26 patients, 14 were operated in emergency and 12 were operated electively. Emergency surgeries were performed after correction of fluid electrolyte imbalance. Of the 14 emergency cases, 3 patients underwent resection anastomosis of small bowel, 6 patients underwent right hemicolectomy for iieocaecal tuberculosis. One patient had a stricturoplasty for ileal stricture in addition to right hemicolectomy. One patient underwent a stricturoplasty for ileal stricture and one unstable patient underwent drain insertion under local anaesthesia to drain out contaminated peritoneal fluid. Remaining two patients underwent adhesiolysis. Conclusions: In this study 60% patients had an acute and subacute presentation and 40% patients had a chronic presentation.